Robot-Assisted Removal of a Partially Intravesical Intrauterine Device (IUD) and Large Bladder Stone. (27th January 2023) - Heaney, Cassandra; Lee, Paul; Winer, Andrew
Abstract : An intrauterine device (IUD) is a highly effective and widely utilized option for long-acting reversible contraception. IUDs are generally well-tolerated with a low rate of serious complications. Perforation of an IUD through the uterine wall and into the urinary bladder is a rare event that may be asymptomatic. The approach for surgical removal primarily depends on the location of the device. We present a case report of a 41-year-old woman who was found to have a partially intravesical IUD and associated 2.4 cm bladder calculus. Removal of the intravesical IUD and stone was achieved with cystoscopy, cystolitholapaxy, and robot-assisted laparoscopic cystotomy.